2012
DOI: 10.1007/s00535-012-0580-5
|View full text |Cite
|
Sign up to set email alerts
|

Timeline for development of autologous bone marrow infusion (ABMi) therapy and perspective for future stem cell therapy

Abstract: Liver cirrhosis patients generally progress to liver failure. To cure this progressive disease, we developed a novel cell therapy using bone marrow cells; autologous bone marrow cell infusion (ABMi) therapy. We previously described the possible action mechanism of ABMi therapy in the cirrhotic liver, and showed the timeline and results of clinical studies of ABMi therapy. We have also carried out other clinical studies using bone marrow cells and granulocyte colony-stimulating factor. Here, we report a new ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…We previously demonstrated the safety and effectiveness of ABMi therapy; we also showed the potential for BMSC to improve liver fibrosis and functioning by carbon tetrachloride induction in non‐obese diabetic/severe combined immunodeficient mice. These results provide a basis for the development of new types of cell therapy using BMSC .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We previously demonstrated the safety and effectiveness of ABMi therapy; we also showed the potential for BMSC to improve liver fibrosis and functioning by carbon tetrachloride induction in non‐obese diabetic/severe combined immunodeficient mice. These results provide a basis for the development of new types of cell therapy using BMSC .…”
Section: Discussionmentioning
confidence: 92%
“…Regenerative therapy is a potential cure for organ failure patients. We have previously reported on the efficacy and safety of autologous bone marrow cell infusion (ABMi) therapy, which has shown promise as a therapeutic strategy for treating liver cirrhosis . However, current ABMi therapy requires the collection of bone marrow by aspiration under general anesthesia, so there are strict criteria regarding the general health of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the establishment of an effective antifibrotic therapy for liver fibrosis remains an unmet clinical requirement. The current focus of basic research is to define a therapeutic target for liver fibrosis, which encompasses suppression of inflammation, 1 control of the HSC activity and proliferation, 8,13,14,15 bone marrow transplantation as an antifibrotic therapy, 8,16 and enhancement of ECM degradation. 2,3,10,17,18,19 …”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been made in recent years to establish cell therapies and gene therapies for liver fibrosis patients in order to reduce fibrotic tissue, recover liver function, and decrease the occurrence of hepatocellular carcinomas. 2,3,4,5,6,7,8 …”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these results, a clinical trial of autologous BMC infusion was conducted, wherein it was shown that BMCs administered through a peripheral vein improved liver function in patients with liver cirrhosis [13,22]. Therefore, BMC infusion may prove to be a curative therapy for liver cirrhosis in the future [27].…”
mentioning
confidence: 99%